Peran Pembimbing Kemasyarakatan Dalam Proses Deradikalisasi Klien Terorisme - Zaki Ahmad Fauzi; Ali Muhammad (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
This research examines the deradicalization program and the role of community counselors in the deradicalization process for terrorism clients in Indonesia. Terrorism is a serious issue that has affected the security and social stability in Indonesia. Therefore, deradicalization programs are crucial in addressing the root causes of terrorism. The research methodology used is a literature review, gathering information from various relevant scholarly publications on the topic of deradicalization. The results of this research reveal that deradicalization programs are planned, integrated, systematic, and ongoing processes aimed at eliminating or reducing radical understanding of terrorism and preventing individuals from returning to terrorist activities. The role of community counselors in deradicalization programs is extremely important. They have a strategic role in guiding and supporting terrorism detainees during their social reintegration programs. In carrying out their duties, community counselors should possess skills such as empathy, active listening, basic counseling, and problem-solving abilities. Moreover, they should also understand the challenges faced by terrorist clients, such as low self-esteem, stigmatization, and lack of family support. Effective deradicalization programs can help reduce the risk of terrorism detainees becoming involved in terrorist activities again after their release. This has significant implications for counterterrorism efforts and strengthens the national security of Indonesia.Peran Pembimbing Kemasyarakatan Dalam Proses Deradikalisasi Klien Terorisme